2018
DOI: 10.1097/htr.0000000000000315
|View full text |Cite
|
Sign up to set email alerts
|

Family History of Migraine Associated With Posttraumatic Migraine Symptoms Following Sport-Related Concussion

Abstract: Family history of migraine is associated with PTM symptoms following sport-related concussion, suggesting a genetic predisposition for migraine may serve as a catalyst or trigger for onset of PTM. However, only presence of PTM, rather than family history of migraine, was related to worse neurocognitive and vestibular/oculomotor outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…Similarly, in a study of 120 young athletes with sports-related concussion, Morgan et al. found that a family history of migraine was more prevalent in the children with persistent post-concussive symptoms compared to those without persistent symptoms (37). In contrast, in a study of 3063 children presenting with an acute head injury at a pediatric emergency department, Zemek et al.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, in a study of 120 young athletes with sports-related concussion, Morgan et al. found that a family history of migraine was more prevalent in the children with persistent post-concussive symptoms compared to those without persistent symptoms (37). In contrast, in a study of 3063 children presenting with an acute head injury at a pediatric emergency department, Zemek et al.…”
Section: Discussionmentioning
confidence: 97%
“…11 Migraine is a headache type characterized by a prodrome and/or aura with associated symptoms including nausea, vomiting, and sensitivity to light, sound, or smell. 12 Pre-existing headache types place individuals at greater risk for headache following a concussion 12,13 or may be worsened following concussion with increasing frequency or severity. Patients with the headache/migraine subtype of concussion have self-reported history of headaches that differs from their pre-existing history and/or changes in their headache assessments demonstrated on validated headache scales with levels of severities.…”
Section: Methodsmentioning
confidence: 99%
“…24 This suggests that head trauma may trigger migraine in those with a genetic predisposition. 24 This suggests that head trauma may trigger migraine in those with a genetic predisposition.…”
Section: Genetic and Phenotypic Backgroundmentioning
confidence: 99%
“…Genetic Influences.-A study of adolescents found that those with a family history of migraine were significantly more likely to have posttraumatic headache with a migraine phenotype following sport-related concussion compared with those without a family history. 24 This suggests that head trauma may trigger migraine in those with a genetic predisposition. Although migraine is clearly familial in many cases, the genetic basis of migraine remains poorly understood.…”
Section: Genetic and Phenotypic Backgroundmentioning
confidence: 99%